2005
DOI: 10.1093/jac/dki288
|View full text |Cite
|
Sign up to set email alerts
|

Activity of posaconazole in the treatment of central nervous system fungal infections

Abstract: These data suggest that posaconazole, as an oral medication, has clinical activity against fungal infections of the CNS and may provide a valuable alternative to parenteral therapy in patients failing existing antifungal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(127 citation statements)
references
References 43 publications
2
118
0
7
Order By: Relevance
“…Since there is interindividual and intra-individual variability in voriconazole plasma levels, therapeutic drug monitoring for voriconazole should be considered in cases of refractory fungal infection or concerns about drug toxicity [147]. Another broad-spectrum triazole, posaconazole, is effective and safe as salvage therapy in patients with IPA refractory to standard antifungal therapy [22,93,125].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is interindividual and intra-individual variability in voriconazole plasma levels, therapeutic drug monitoring for voriconazole should be considered in cases of refractory fungal infection or concerns about drug toxicity [147]. Another broad-spectrum triazole, posaconazole, is effective and safe as salvage therapy in patients with IPA refractory to standard antifungal therapy [22,93,125].…”
Section: Treatmentmentioning
confidence: 99%
“…According to the recent statement of the American Thoracic Society for treating fungal infections in adults [123], the duration of IPA therapy should be individualised to the Continuation therapy: voriconazole or itraconazole [122,123] Salvage therapy: echinocandin or posaconazole [125][126][127] Chronic necrotising aspergillosis Voriconazole [120,123] Alternative therapy: itraconazole [128,129] Severe cases: intravenous voriconazole or liposomal amphotericin B [123,128,130] Consider surgical resection [130] Aspergilloma Observation [123] Bronchial artery embolisation [131] Surgical resection [132][133][134][135] Consider itraconazole [136][137][138] Allergic bronchopulmonary aspergillosis Corticosteroids [139][140][141][142] Itraconazole or voriconazole as steroid-sparing agents [143][144][145][146] Surgical resection has generally a limited role in the management of patients with IPA, but it becomes important in cases with invasion of bone, burn wounds, epidural abscesses and vitreal disease [123]. It should also be considered in cases of massive haemoptysis, pulmonary lesions close to the great blood vessels or pericardium, or residual localised pulmonary lesions in patients with continuing immunosuppression or those who are expected to have immunosuppressive therapy in the future.…”
Section: Treatmentmentioning
confidence: 99%
“…ABLC demonstrated a total response of 66% in 101 patients, 75% in 44 cases of first-line therapy (BII) [4]. Posaconazole was effective in 14 from 29 patients [83]; voriconazole data are very limited (CIII). In isolated pulmonary cryptococcosis, fluconazole 200-400 mg for 6-12 months may be sufficient (AIII) [45,95]; alternatively, itraconazole 200-400 mg may be used (BIII).…”
Section: Cryptococcus Neoformans Infectionsmentioning
confidence: 99%
“…This is thought to be due to pharmacokinetics of the drug, combined with host factors. An open label clinical trial of the efficacy of posaconazole in the treatment of patients with CNS fungal infections showed that posaconazole was successful in 48% (14 of 29) of the patients with cryptococcal infection and in 50% (5 of 10) of patients infected with other fungal pathogens [20]. However, posaconazole is not currently approved for this indication [21].…”
Section: Discussionmentioning
confidence: 99%